Retinal Disorders in a Tertiary Eye Centre in Nigeria - Oluwole Oluseye Ajogbasile, Iyiade Adeseye Ajayi, Olusola Joseph Omotoye, Kayode Olumide Ajite (Pakistan Journal of Ophthalmology, 2016)
Purpose: To review the types of retinal disorders in patients seen at the retinal clinic of a tertiary eye centre in southwestern Nigeria. Study Design: Observational descriptive study. Place and Duration of Study: The record kept at the retinal clinic of the Ekiti State University Teaching Hospital over a 2½ year period from July 2013 to January 2016 was reviewed. Materials and Methods: All patients seen in the clinic had documentation of their demographic characteristics, visual acuity at presentation, findings on dilated fundus examination, slit lamp biomicroscopy and diagnosis. Results: A total of 405 patients constituting 10.4% of the total patient load had retinal disorders during the period of study. The mean age was 56.95 ± 20.8 years. More than half (68.5%) of the patients were aged 50 years and above. The presenting visual acuity was < 3/60 in 135 (33.3%) of cases. Age related Macular Degeneration was the leading eye disorder seen in 18.2% followed closely by Diabetic retinopathy in 16.3%. Retinitis pigmentosa was the leading cause of bilateral blindness. Optical Coherence Tomography (67.4%) and Fundus Fluorescein Angiography (61.73%) were the leading investigations ordered in the retinal clinic. Conclusion: Age related macular degeneration and diabetic retinopathy were the leading eye disorders in our centre. Limited access to Investigative facilities is a major challenge in the management of retinal disorders in our centre. Keywords: Retinal disorders, tertiary eye, retinal investigations.